Toward leader democracy - Pakulski, Jan 1950- (Anthem Press, 2012)
Toward Leader Democracy investigates how todays liberal democratic regimes are increasingly moving toward a pronounced focus on political leaders and their image, and explores the mechanics, evolution and implications of this phenomenon
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Democracy; Political leadership; Demokratie; Politische Führung